A British education control officer in occupied Germany, 1945-1949 : the letters of Edward Aitken-Davies - Phillips, David, 1944 December 15- (2024)
"Edward Aitken-Davies (1899-1981) served as an Education Control Officer in the British Zone of occupied Germany from the early summer of 1945 until December 1949. He thus experienced the implementation of policy in the Zone from the very beginnings of the occupation until the founding of the Federal Republic of Germany in 1949. During the period 1945 to 1947 he wrote weekly letters home to his mother. Those letters, together with the many speeches he gave in Germany during his time as a leading British officer in the Hanover region have not hitherto been available to researchers but can now be made accessible in edited form. The letters are placed in the context of developments in British policy and with explanatory notes on the detail. Taken together, his letters and other documents provide insights into the day-to-day lives of the impressive group of individuals who oversaw the development of education in Germany from post-war chaos to the reform and stability which restored the education system of the country to a pre-eminent status in Europe"--
Introduction -- Education in the British Zone of Germany, 1945-1949 -- Edward Aitken-Davies, 1899-1981 -- Edward Aitken-Davies's letters to his mother, May 1945-December 1947 -- Postscript, 1948-1949 and after -- Appendices A. EAD : lecture on his work in Germany, 1945-1949 -- B. EAD : outline of the views of the German political parties on the subject of educational reform (July 1948) -- C. EAD : thoughts on the British Relations Board scheme.
Includes bibliographical references and index.
Keywords: Aitken-Davies, Edward, -- 1899-1981 -- Correspondence; Education and state -- Germany -- History -- 20th century; Educational change -- Germany -- History -- 20th century; Germany -- History -- 1945-1955.; British -- Germany -- Hanover (Province) -- History -- 20th century; Educators -- Great Britain -- Correspondence; Educators -- Germany -- Correspondence; Personal correspondence